Competitiveness in the new economy - Petri Rouvinen (The Research Institute of the Finnish Economy (ETLA), 2002)
This paper devises an e-competitiveness index attempting to measure the ability of a nation to exploit information and communication technology (ICT) to the fullest. Results of the analysis show that Finland is highly specialized in ICT provision, it has good premises to exploit ICT to the fullest, but that it is not amongst the leading users of ICT. – Internet ; ICT ; IT ; new economy ; competitiveness ; e-competitiveness
Keywords: 330; Internationaler Wettbewerb; Theorie; New Economy